Seasonality of Children’s Height and Weight and Their Contribution to Accelerated Summer Weight Gain - Moreno, Jennette P.; Musaad, Salma; Dadabhoy, Hafza; Baranowski, Tom; Crowley, Stephanie J.; Thompson, Debbe; Chen, Tzuan A.; Johnston, Craig A. (Frontiers in Physiology, 2022)
Background: While children have been shown to have increased BMI during the summer compared to the school year, it is not known if this may be due to seasonal variations in height or weight separately. Methods: Trained nurses measured heights (cm) and weights (kg) in a cohort of Kindergarteners (n=7599) twice per year from the beginning of kindergarten through 5th grade. Variation in height and weight by season (school year vs summer) was examined using separate mixed-effects models. Season, sex, and BMI trajectory group were tested as fixed effects. Random effects included repeated measurements of time, students nested within a school, intercept, and slope for growth over time. Similar models using BMIz as the outcome examined the interaction of height or weight with season. Results: The rate of height gain was greater during the school year (~Sept to April) compared to summer (~April to Sept) (β = -0.05, SE=.013, p<0.0001). The rate of weight gain did not differ seasonally. Height gain was more strongly associated with increased BMIz during summer compared to the school year (β =.02, SE=0.005, p<.0001), mainly among children who remained healthy weight throughout elementary school (β=0.014, SE=0.003, P<0.0001) and those who transitioned to a healthier weight status (β=0.026, SE=0.008, P=0.004). We found a similar seasonal effect for the association between weight with BMIz (β=0.016, SE=0.003, P<0.0001), particularly among children who maintained a healthy weight status (β=0.014, SE=0.014, P<0.0001). Conclusion: This study indicates seasonality in children’s height gain, gaining height at a faster rate during the school year compared to the summer, while weight gain remained relatively more consistent throughout the year. Seasonality in height and weight gain had the greatest impact on BMIz among children with a healthy weight status. Future research with more frequent measurements is needed to better understand the seasonal regulation of children’s growth and weight gain.